Between-event and between-station variability observed in the Fourier and response spectra domains: comparison with seismological models. Issue 2 (18th May 2017) - Bindi, D.; Spallarossa, D.; Pacor, F.
Abstract: In this study, we analyse a regional data set composed by about 9000 waveforms from 231 earthquakes in the magnitude range from 3 to 6 and recorded in central Italy in the time period 2008–2013. We derive a seismological model whose source, attenuation and site parameters are used to explain the ground motion variability associated with a set of ground motion prediction equation (GMPE) calibrated ad hoc for both Fourier and acceleration response spectra. The main results are the following: (1) the between-event residuals δΒe show a clear dependence on the stress drop for frequencies above 2 Hz; (2) the standard deviation τ of δΒe is strongly reduced (up to 80 per cent) by introducing in the functional form the stress drop values estimated from each source spectrum; (3) the standard deviation τ depends on the magnitude scale used to calibrate the GMPE: while the moment magnitude better describes the source variability at low frequency, the local magnitude better capture the source-related ground motion variability at frequencies larger than 2 Hz; (4) for frequencies higher than 10 Hz, the observed increase of τ with frequency correlate well with the attenuation parameter k source, computed from the high-frequency slope of the source spectra. Regarding the station-to-station residuals δS2S, their frequency dependency is in good agreement with the site amplifications extracted from the S -wave spectra. Finally, while the overall dependences of the ground motion variability on seismological parameters are similar when observed either in the Fourier or in the response spectra domains (e.g. the dependency of the between event on stress drop), differences in the results suggest that the response spectra do not allow to fully capture the ground motion variability, as well as the site amplifications, at high frequencies.